PENGARUH MEDIA PERMAINAN ULAR TANGGA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA MATA PELAJARAN IPAS KELAS V SD NEGERI BEROANGING KOTA MAKASSAR - Tasriani; Hotimah; Muhammad Amin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the problem of low conceptual understanding among students in the IPAS subject, where learning is predominantly teacher-centered and relies heavily on lecturing without the use of instructional media. As a result, students tend to memorize information rather than deeply understand the material and are less actively engaged in the learning process. This research aims to describe the implementation of the snakes and ladders game as a learning medium in IPAS, to examine students’ conceptual understanding during the learning process, and to determine the influence of this medium on improving conceptual understanding among fifth-grade students at SD Negeri Beroanging, Makassar City.The findings indicate that the use of the snakes and ladders game effectively transformed the learning environment into a more active and collaborative setting. Students demonstrated increased enthusiasm, more frequent participation in discussions, and improved ability to answer conceptual questions meaningfully. Posttest results from the experimental class showed a significant increase compared to the control class, which continued using conventional learning methods. Statistical analysis using the Independent Sample T-Test confirmed a significant difference between the two groups, indicating that the game-based medium positively influenced students’ conceptual understanding.In conclusion, the snakes and ladders game is proven to be an effective alternative instructional medium for IPAS learning. It not only enhances students’ conceptual understanding but also fosters motivation, self-confidence, and active participation in learning, making it worth applying to improve the quality of learning in elementary schools.